Membangun Ekosistem E-Commerce Shopee yang Berkeadilan: Rekonstruksi Perlindungan Hak Intelektual atas Pemalsuan Produk Skincare melalui Pendekatan Ekonomi Digital - Tabansa, Claudya Vanessa; Moh Sabil Oktaviano; Denta Nia Aprilya; Muhammad Adymas Hikal Fikri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The rapid growth of the digital economy has significantly increased commercial activities on e-commerce platforms, including the skincare sector, which remains one of the most in-demand product categories. However, this expansion has also led to the widespread circulation of counterfeit skincare products, causing harm to consumers, brand owners, and the overall integrity of the digital marketplace ecosystem. This study aims to analyze the effectiveness of copyright protection against counterfeit skincare products on Shopee, examine the role of e-commerce platforms in fostering a fair and secure digital ecosystem, and identify the key barriers to reconstructing legal protection within the framework of the digital economy. This research employs normative and empirical legal methods through regulatory review, interviews, observations, and document analysis. The findings reveal that although legal frameworks are in place, their implementation remains suboptimal due to weak seller verification, insufficient digital monitoring, and low deterrent effects of sanctions. The study highlights the urgency of strengthening intellectual property protection through technological integration, such as artificial intelligence and blockchain, to support a safer and more equitable digital marketplace.